2014
DOI: 10.1002/anie.201310275
|View full text |Cite
|
Sign up to set email alerts
|

Copper‐Catalyzed Cross‐Coupling of Boronic Esters with Aryl Iodides and Application to the Carboboration of Alkynes and Allenes

Abstract: Copper-catalyzed Suzuki–Miyaura-type cross-coupling and carboboration processes are reported. The cross-couplings function well with a variety of substituted aryl iodides and aryl boronic esters and allows for orthogonal reactivity compared to palladium-catalyzed processes. The carboboration method includes both alkynes and allenes and provides access to highly substituted and stereodefined vinyl boronic esters. The alkyne carboboration method is highlighted in the simple one-pot synthesis of Tamoxifen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
78
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 243 publications
(80 citation statements)
references
References 89 publications
2
78
0
Order By: Relevance
“…Our reaction tolerated a variety of functional groups and proceeded with both electron-rich and electron-poor coupling partners, consistently affording the coupled products in good to excellent yields. Recently, a similar coupling of arylboronate esters with aryl iodides was also reported by Brown et al 31 Consistent with the reactivity trend observed for the coupling of arylsilicon reagents, the reactions of heteroarylboron reagents and heteroaryl iodides proceeded in good to excellent yields by using only 2 mol% copper(I) iodide as catalyst and without requiring the addition of P,N-ligands (Scheme 4). The reaction tolerates functional groups such as CF 3 and ethers on both coupling partners as well as chloride on heteroaryl iodides.…”
Section: Coupling With Organoboron Reagentssupporting
confidence: 69%
“…Our reaction tolerated a variety of functional groups and proceeded with both electron-rich and electron-poor coupling partners, consistently affording the coupled products in good to excellent yields. Recently, a similar coupling of arylboronate esters with aryl iodides was also reported by Brown et al 31 Consistent with the reactivity trend observed for the coupling of arylsilicon reagents, the reactions of heteroarylboron reagents and heteroaryl iodides proceeded in good to excellent yields by using only 2 mol% copper(I) iodide as catalyst and without requiring the addition of P,N-ligands (Scheme 4). The reaction tolerates functional groups such as CF 3 and ethers on both coupling partners as well as chloride on heteroaryl iodides.…”
Section: Coupling With Organoboron Reagentssupporting
confidence: 69%
“…1 H and 13 C NMR spectra and melting point are in agreement with the published data. 12 2 (4 Bromophenyl)naphthalene (4c). Yield 51%, m.p.…”
mentioning
confidence: 99%
“…While carbene ( e. g ., C−M−C) and CO (X−M−CO) ligands still induce the largest shifts toward strong and weak binding, respectively, catalyst with two phosphine ligands (P−M−P) in tandem with a group 11 metal are shifted toward stronger, rather than weaker, binding. This non‐intuitive behavior of phosphine ligands may explain experimental observations of Cu catalyzed Suzuki‐Miyaura C−C cross‐couplings with phosphine ligands . Overall, the clearest route to improving the thermodynamic profiles of group 11 catalysts is including strong σ‐donating ligands that result in stronger binding between the catalyst and the substrate.…”
Section: Resultsmentioning
confidence: 92%